THE USE OF CONNECTIVES IN LITERARY SPEECH. ("Conference on Universal Science Research 2023", 2023)
Connectives or connective words are words or phrases that link sentences or clauses together. Connectives can be conjunctions, prepositions, or adverbs and are used frequently both in spoken and written English. Connectives are functional words that help a writer link their words together. They serve as the glue of the sentence as they help words to flow and lead on from one to another without sounding awkward or unclear. Without connectives, a written sentence or spoken sentence wouldn't make very much sense. Using connectives strengthens writing skills.